The redefined DNA‐binding domain of human xeroderma pigmentosum complementation group A: production, crystallization and structure solution. Issue 1 (3rd January 2019) - Lian, Fu-Ming; Yang, Xiangwei; Yang, Wancai; Jiang, Yong-Liang; Qian, Chengmin
Abstract : The redefined DNA‐binding domain (residues 98–239) of human xeroderma pigmentosum complementation group A, a scaffold protein that plays significant roles in DNA‐damage verification and recruiting downstream endonucleases to facilitate the repair of DNA lesions in nucleotide‐excision repair, was produced and crystallized and its structure was solved. Abstract : Human xeroderma pigmentosum complementation group A (XPA) is a scaffold protein that plays significant roles in DNA‐damage verification and in recruiting downstream endonucleases to facilitate the repair of DNA lesions in nucleotide‐excision repair. XPA98–219 (residues 98–219) has been identified as a DNA‐binding domain and has been extensively studied in the last two decades. However, the most recent studies have redefined the DNA‐binding domain as XPA98–239 (residues 98–239); it exerts a remarkably higher DNA‐binding affinity than XPA98–219 and has a binding affinity that is quite similar to that of the full‐length protein. Here, the production, crystallization and structure solution of human XPA98–239 are described. Crystals were obtained using a precipitant composed of 1.8 M ammonium citrate tribasic pH 7.0. Native X‐ray diffraction data and zinc single‐wavelength anomalous diffraction (SAD) data were collected to 1.93 and 2.06 Å resolution, respectively. The crystals belonged to space group P 3, with unit‐cell parameters a = 67.1, b = 67.1, c = 35.6 Å, γ = 120.0°. Crystal‐content analysis showed the presence of one molecule in the asymmetric unit, corresponding to a Matthews coefficient of 2.65 Å 3 Da −1 and a solvent content of 53.6%. The initial phases were solved and the structure model was automatically built by zinc SAD using the AutoSol program. The initial structure model covered 119 of 142 residues in the asymmetric unit, with an R work of 22.15% and an R free of 25.82%. Compared with a previously obtained truncated solution NMR structure of XPA (residues 98–210), a 19‐residue C‐terminal extension (residues 211–229, corresponding to 10 of the 20 extra C‐terminal residues in the redefined domain for enhanced DNA binding) was contained in this initial model. Refinement of the atomic coordinates of XPA is ongoing.